Understanding the Organisation and Role of Myosin Binding Protein C in Normal Striated Muscle by Comparison with MyBP-C Knockout Cardiac Muscle - Luther, Pradeep K. (Elsevier, 2008)
Myosin binding protein C (MyBP-C) is a component of the thick filament of striated muscle. The importance of this protein is revealed by recent evidence that mutations in the cardiac gene are a major cause of familial hypertrophic cardiomyopathy. Here we investigate the distribution of MyBP-C in the A-bands of cardiac and skeletal muscles and compare this to the A-band structure in cardiac muscle of MyBP-C-deficient mice. We have used a novel averaging technique to obtain the axial density distribution of A-bands in electron micrographs of well-preserved specimens. We show that cardiac and skeletal A-bands are very similar, with a length of 1.58 ± 0.01 μm. In normal cardiac and skeletal muscle, the distributions are very similar, showing clearly the series of 11 prominent accessory protein stripes in each half of the A-band spaced axially at 43-nm intervals and starting at the edge of the bare zone. We show by antibody labelling that in cardiac muscle the distal nine stripes are the location of MyBP-C. These stripes are considerably suppressed in the knockout mouse hearts as expected. Myosin heads on the surface of the thick filament in relaxed muscle are thought to be arranged in a three-stranded quasi-helix with a mean 14.3-nm axial cross bridge spacing and a 43 nm helix repeat. Extra “forbidden” meridional reflections, at orders of 43 nm, in X-ray diffraction patterns of muscle have been interpreted as due to an axial perturbation of some levels of myosin heads. However, in the MyBP-C-deficient hearts these extra meridional reflections are weak or absent, suggesting that they are due to MyBP-C itself or to MyBP-C in combination with a head perturbation brought about by the presence of MyBP-C.